2020
DOI: 10.1093/europace/euaa162.044
|View full text |Cite
|
Sign up to set email alerts
|

P1097Heart rate acceleration is a poor surrogate of complete parasympathetic denervation of sinus node during cardioneuroablation

Abstract: Background Ablation of superior paraseptal ganglionic plexi is invariantly associated with the acceleration of sinus rhythm. This is considered a favourable sign during cardioneuroablation for the treatment of recurrent neurally-mediated cardioinhibitory syncope or symptomatic sinus bradycardia. Purpose In this retrospective study, we investigated whether the magnitude of sinus rhythm acceleration corresponds with directly as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Immediate results may be achieved by eliminating superficial fibers, but long‐term outcomes depend on the disappearance of deep neural bodies. There are numerous instances where, despite modifications in all EP parameters, ECVS reveals a significant residual vagal response, 28 often leading to clinical recurrence. In this study, we found that although there was no statistically significant difference in the electrophysiological parameters of acute vagal denervation (as shown in Table 3), there was a significant difference in long‐term outcomes, suggesting that immediate electrophysiological response alone may not be enough to predict the long‐term efficacy of CNA.…”
Section: Cna Without Ecvsmentioning
confidence: 99%
“…Immediate results may be achieved by eliminating superficial fibers, but long‐term outcomes depend on the disappearance of deep neural bodies. There are numerous instances where, despite modifications in all EP parameters, ECVS reveals a significant residual vagal response, 28 often leading to clinical recurrence. In this study, we found that although there was no statistically significant difference in the electrophysiological parameters of acute vagal denervation (as shown in Table 3), there was a significant difference in long‐term outcomes, suggesting that immediate electrophysiological response alone may not be enough to predict the long‐term efficacy of CNA.…”
Section: Cna Without Ecvsmentioning
confidence: 99%
“… 3 CNA must be finished only after complete vagal response abolishment, and no CNA may be considered successful without this confirmation as the main endpoint. In case of residual vagal response, CNA must be expanded, ablating additional atrial fibrillation nests, 4 , 5 , 6 until complete abolishment. Residual innervation must be disclosed to the patient, as reinnervation/recurrence may occur.…”
mentioning
confidence: 99%